THE IMPACT OF URBANIZATION ON INCOME DISTRIBUTION: A STUDY OF GEORGIA (International Journal of Innovative Technologies in Economy, 2024)
In the current decades, the world's rapid urbanization is the greatest challenge to ensuring human welfare and sustainable development. Urban areas offer better market structures, and there is evidence that workers in urban areas are more productive, and earn more, than rural workers. Clearly, the proportion of a country's population living in urban areas is correlated with its income level. Although, rapid urbanization is associated with crowding, environmental degradation, and other impediments to productivity.This paper studies urbanization and income distribution in Georgia. Research explores the impact of urbanization on income distribution in Georgia using multiple regression analysis. The research data covers 11 regions of Georgia. Our findings emphasize the role of urbanization, economic growth, and human capital in the process of income distribution. The results show that urbanization has an impact on income distribution and accordingly can reduce income inequality.    We find evidence that the level of urbanization affects the rate of economic growth.